2021
DOI: 10.1101/2021.03.19.21253391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of porcine delta-coronavirus pathogenic infections among children in Haiti through independent zoonoses and convergent evolution

Abstract: Coronaviruses have caused three major epidemics since 2003, including the ongoing SARS-CoV-2 pandemic. In each case, coronavirus emergence in our species has been associated with zoonotic transmissions from animal reservoirs, underscoring how prone such pathogens are to spill over and adapt to new species. Among the four recognized genera of the family Coronaviridae (Alphacoronavirus, Betacoronavirus, Deltacoronavirus, Gammacoronavirus), human infections reported to date have been limited to alpha and betacoro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 56 publications
(93 reference statements)
1
52
0
Order By: Relevance
“…Coronaviruses have long been known to present a high pandemic risk. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the ninth documented coronavirus that infects humans and the seventh identified in the last 20 years (Lednicky et al, 2021;Vlasova et al, 2021). All previous human coronaviruses have zoonotic origins, as have the vast majority of human viruses.…”
Section: Evidence Supporting a Zoonotic Origin Of Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Coronaviruses have long been known to present a high pandemic risk. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the ninth documented coronavirus that infects humans and the seventh identified in the last 20 years (Lednicky et al, 2021;Vlasova et al, 2021). All previous human coronaviruses have zoonotic origins, as have the vast majority of human viruses.…”
Section: Evidence Supporting a Zoonotic Origin Of Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Human-to-mink transmission and vice versa has occurred (6). At least nine CoVs are known to infect humans, including three highly virulent strains [SARS-CoV-1 and SARS-CoV-2 and Middle East respiratory syndrome (MERS)-CoV], four viruses (229E, HKU1, NL63, and OC43) that elicit mild common cold symptoms (7), and two others for which cases of human transmission have been reported (8,9). Likely because of differences in their spike and nucleoproteins (7,10), SARS-CoV and MERS-CoV can precipitate severe lower respiratory tract illness, immune exhaustion, systemic hyperinflammation, cytokine storm/cytokine response syndrome (CRS), multiorgan failure, and death.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that PDCoV could limitedly infect mice in vivo and could be passaged in six-day-old embryonated chicken eggs (ECEs) with high viral replicative efficiency [ 26 , 27 ]. A recent study reported that PDCoV was identified in plasma samples of three Haitian children with acute undifferentiated febrile illness, demonstrating the infection of PDCoV in humans [ 28 ]. These studies suggest that PDCoV possesses the potential for cross-species transmissibility.…”
Section: Introductionmentioning
confidence: 99%